Effect of Occupational Safety and Health Procedures on Fabric Dyeing Process in Reducing Worker Fatigue at the TBS Textile Factory - Ni Luh Gede Aris Maytadewi Negara; I.A. Pascha Paramurthi; Ni Ketut Putri Purnama Dewi (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: TBS textile factory is one of several textile factories where the process of fabrics dyeing takes place. In the process, workers lift and transport cloth loads manually, and thus work routines make their body bend. TBS textile factory ignored the health and safety aspects of work procedures which could cause worker fatigue. Safe work behaviour may prevent occupational sickness if the company applies appropriate occupational safety and health procedures. The purpose of this study was to determine the reduction of worker fatigue in the dyeing process of woven fabrics by applying occupational safety and health procedures. Methods: This study used treatment by subject design, where all samples were subjected to control and treatment, in different time periods. In this design, the interval between the time periods required washing out and adaptation, to eliminate the effects of previous work. The research population were workers in charge of dyeing section at TBS textile factory located in Gianyar regency. This study was conducted in July 2021 by involving 20 samples selected through purposive sampling technique. Data were collected from occupational safety and health procedures (how workers lifted and transported loads), legal limitations, and worker postures. Data analysis was carried out using t-independent test. Results: There was a decrease in scores of worker fatigue. The two different tests showed the scores after the study were significantly different (p < 0.05). Conclusion: Occupational safety and health procedures can reduce fatigue among workers in charge of fabrics dyeing by 40.77%.